Accounting principles - Weygandt, Jerry J. (John Wiley & Sons, Inc., 2002)
Revised edition of a textbook for the introductory college-level course in accounting principles. In addition to the use of color throughout, chapter study aids include concepts for review, chapter- opening vignettes, study objectives, technology in action sections, marginal hints, accounting in action boxes, review questions, international notes, ethics notes, glossaries, demonstration problems, self-study questions, exercises, problems, financial reporting cases, decision cases, ethics cases, critical thinking cases, communication activities, group activities, and answers to self-study questions. Numerous student supplements are available.